L’avenir est à ceux qui l’auront préparé - Ross, Jacques (Assurances, 1987)
The Life Insurance industry, in the last ten years, has been extremely profitable for the insurers based in part on high interest rates and inflation. Those days are over and the size of our industry and the extreme competition have made it almost impossible to keep such a pace. The financial institutions are realigning their planification to take advantage of the cross ownership that will be made possible between types of institutions in the near future at the Federal level. Banks, insurance companies, trust companies and brokerage firms will compete through mergers or acquisitions to take advantage of the new legislation. The future belongs to the institutions that already have taken advantage of the last year or two to prepare the next five or ten.